Joint Use of e.Photoexpression© and Photonarration: What Methodological Added Value? - Maéliane, Deyra; Chloé, Gay; Laurent, Gerbaud; Pauline, Berland; Frank, Pizon (Frontiers in Public Health, 2021)
Objectives: The objective is to describe the informative value and the added value of a qualitative multiphase methodology in order to investigate the conceptions of children aged 6 to 11 on the determinants of health and cancer. Method: This article provides an analysis of the "Determ'Ados" research protocol, a qualitative study in human and social sciences, carried out with children aged 6 to 11 years. This protocol, organized in three phases, addresses in the first global health with the tool "e.Photoexpression ©", in the second questions and knowledge around the topic of cancer with the tool "QC" and in the third cancer again with the "Photonarration" tool. The methodology of this innovative, open and exploratory research protocol aims to collect data relating to the experiences, declared practices and knowledge specific to each child who express themselves through photography and storytelling. Results: The analysis of the Determ'Ados methodology shows that the level of collection is important and that it brings results from CP to CM2: 1498 productions (4 productions per child) were distributed to 381 children with a wealth in the data available thanks to the multiphase protocol. This mass qualitative collection brings complementarity as the collection phases progress and guarantees continuity in the discourse of each child which allows them to deepen their conceptions and to know how they create or not meaning between the determinants of health and cancer. Perspectives: The density and quality of the proposals collected from the children reinforce the validity and rigor of the Determ'Ados methodology. Multiphase is the innovative aspect of the tools used. The e.Photoexpression © and the Photonarration are complementary and inseparable to bring out concepts on health and cancer. These research results, transferable into interventions and current practices, present prevention officers to act more effectively, closer to the conceptions and needs of children.